Experienced Well-Being and Labor Market Status: The Role of Pleasure and Meaning - Tobias Wolf; Maria Metzing; Richard E. Lucas (Social Indicators Research, 2022)
This paper examines the experienced well-being of employed and unemployed workers. We use the survey-adapted Day Reconstruction Method of the Innovation Sample of the German Socio-Economic Panel Study to analyze the role of the employment status for well-being, incorporating time use. We use the novel P-index to summarize the average share of pleasurable minutes on a day and show that in contrast to evaluative life satisfaction the unemployed experiences more pleasurable minutes due to the absence of working episodes. Hence, we examine working episodes in depth. While working is among the activities with the highest propensities for an unpleasant experience, it is also among the most meaningful activities. We show that meaning is a central non-monetary determinant for pleasure at work and find that pleasure during work and job satisfaction have a comparable association with meaning.
Keywords: 300; Experienced well-being; Time use; Unemployment; Day reconstruction method; DRM; SOEP-IS